Diagnosis, Management, and Treatment of Vernal Keratoconjunctivitis in Asia: Recommendations From the Management of Vernal Keratoconjunctivitis in Asia Expert Working Group - Mehta, Jodhbir S.; Chen, Wei-Li; Cheng, Arthur C. K.; Cung, Le Xuan; Dualan, Ivo J.; Kekunnaya, Ramesh; Khaliddin, Nurliza; Kim, Tae-Im; Lam, Douglas K.; Leo, Seo Wei; Manurung, Florence; Tesavibul, Nattaporn; et al. (Frontiers in Medicine, 2022)
Vernal keratoconjunctivitis (VKC) is an underdiagnosed and underrecognized ocular surface disease with limited epidemiological data in Asia. It is more prevalent in warm, dry, and windy climates, and often has a substantial impact on a patient’s quality of life. In rare cases, VKC can be associated with vision loss, either through corticosteroid overuse or inadequate treatment of persistent inflammation. As a potentially severe and complex disease, there is variability with how VKC is managed across Asia and among the various allergic eye diseases. Diagnosis and treatment of patients with VKC is a challenge for many ophthalmologists, since no precise diagnostic criteria have been established, the pathogenesis of the disease is unclear, and anti-allergic treatments are often ineffective in patients with moderate or severe disease. In addition, the choice of treatment and management strategies used for patients varies greatly from country to country and physician to physician. This may be because of a lack of well‑defined, standardized guidelines. In response, the Management of Vernal Keratoconjunctivitis in Asia (MOVIA) Expert Working Group (13 experts) completed a consensus program to evaluate, review, and develop best-practice recommendations for the assessment, diagnosis, and management of VKC in Asia. The expert-led recommendations are summarized in this article and based on the currently available evidence alongside the clinical expertise of ophthalmologists from across Asia with specialism and interest in the ocular surface, VKC, and pediatric ophthalmology.